0227 Sleep Deprivation Enlarges Inter-stimulus Interval Effect On Vigilant Attention. (27th April 2018) - Yang, F; Xu, S; Basner, M; Chai, Y; Dinges, D F; Rao, H
Abstract: Introduction: Sleep deprivation (SD) significantly impairs vigilance attention and reduces the ability to maintain a consistent alertness level. The Psychomotor Vigilance Test (PVT) is a widely used and highly sensitive vigilance task for sleep studies, which records reaction times (RT) to visual stimuli that occurs at random inter-stimulus intervals (ISI). Previous studies have shown that longer ISI facilitates faster RT on the PVT. Although the negative effects of sleep loss on PVT performance have been well documented, whether and how SD modulates the ISI effect on vigilant attention remain elusive. Here we studied this question using a large PVT data set. Methods: Seventy health adults (33.9 ± 8.8y, 41 males) participated in a 5-day and 4-night in-laboratory controlled sleep study, including n=54 in the experimental group involving 36-hour of acute total SD (TSD) followed by two nights of recovery sleep, and n=16 in the control group without SD. All participants completed a cognitive test battery every 2 hours while awake, including a 10-min standard PVT and a 3-min brief PVT (PVT-B). A total of 1766 PVT and 1622 PVT-B tests data were included. The linear approach to threshold with ergodic rate (LATER) model was used to fit the data. Results: Reliable effects of ISI on vigilant attention were found for the PVT and PVT-B in both experimental and control groups, such that RT decreased monotonically with longer ISI. The LATER model indicated that changes in perceptual sensitivity rather than threshold adjustment may underlie this ISI effect. A larger ISI effect was found for PVT tests after TSD compared to those after baseline or recovery sleep ( p <0.001), whereas no differences were found between PVT tests after baseline or recovery sleep in the SD group, nor among PVT tests on different days in the control group. Conclusion: Our results suggest that sleep deprivation increases the ISI effect on both standard 10-min and brief 3-min PVT, which may be due to altered perceptual sensitivity of time intervals after sleep loss. Support (If Any): Supported in part by NIH grants R01-HL102119, R01-MH107571, R01-NR004281, and CTRC UL1RR024134.